The mistaken history of the Korean War what we got wrong then and now - Edwards, Paul M. (McFarland & Company, Inc., Publishers, 2018)
"Intense propaganda and limited press coverage during the Korean War, coupled with vague objectives and an incomplete victory, resulted in a popular narrative of partial truth and factual omission. Battlefield stories...essentially true but often missing significant information...added an element of myth. Drawing on a range of sources, the author reexamines the war's causes, costs and outcomes"...
Includes bibliographical references and index
Keywords: Korean War, 1950-1953; Korean War, 1950-1953 -- Historiography; Koreakrieg